2019
DOI: 10.1111/jace.16284
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of 2D Ruddlesden‐Popper perovskite (BA)2(FA)n−1PbnI3n+1 compounds for photovoltaic applications

Abstract: 2D-3D-structured formamidine perovskite composites are highlighted due to their enhanced stability in solar cell applications. However, the structural and optical properties of 2D formamidine perovskites remain unclear. In this work, we developed new formamidine-based Ruddlesden-Popper perovskite compounds (BA) 2 (FA) n−1 Pb n I 3n+1 (n ≤ 4) using hot-spin coating. Orthorhombic 2D-layered perovskites were formed with a mixture of 3D formamidine perovskite from (BA) 2 (FA) n−1 Pb n I 3n+1 precursors. Their form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that processing solvents play a significant role in the control of the formation of perovskite films, signaling that the high quality of RP perovskite films can be achieved by the rational selection of the processing solvents. [ 187 ] A binary solvent engineering of DMF and DMSO in the precursor solution has become a popular and promising choice to prepare high‐quality RP perovskite films. Of note, this method is particularly used to fabricate RP perovskite films with high n value as the binary solvent engineering can overcome the difficulty of the decreased crystallinity and the declined vertical growth orientation with increasing n as mentioned in the section The Value of n .…”
Section: Strategies To Fabricate High‐quality Rp Perovskite Film In Pscsmentioning
confidence: 99%
“…It has been demonstrated that processing solvents play a significant role in the control of the formation of perovskite films, signaling that the high quality of RP perovskite films can be achieved by the rational selection of the processing solvents. [ 187 ] A binary solvent engineering of DMF and DMSO in the precursor solution has become a popular and promising choice to prepare high‐quality RP perovskite films. Of note, this method is particularly used to fabricate RP perovskite films with high n value as the binary solvent engineering can overcome the difficulty of the decreased crystallinity and the declined vertical growth orientation with increasing n as mentioned in the section The Value of n .…”
Section: Strategies To Fabricate High‐quality Rp Perovskite Film In Pscsmentioning
confidence: 99%
“…98 During the crystal growth process, a low supersaturation condition is required to maintain continuous crystal growth along the vertical direction without any other nucleation. 99 In devices fabrication, the adjustment of supersaturation can be achieved by controlling the rate of solvent evaporation, and more specically, by controlling the additive type 100,101 and quantity, 102 solvent ratio, 103,104 and substrate preheating temperature. 97 As previously discussed in thin lms, there are various coexisting phases with different n values and the proposed energy funnelling effect plays an important role in highly efficient carrier transport, making it difficult to specify the contributions from each phase or other interplay factors such as the energy funnelling effect.…”
Section: Solar Cellsmentioning
confidence: 99%
“…The aforementioned factors act as a guideline for optimizing PSCs in terms of developing efficient interlayer materials and feasible interfacial engineering through surface passivation that contributes to suppressing the structural defects and improving the quality and chemical stability of perovskite films, which can further help to eliminate the interfacial energy barriers, reduce trap density and nonradiative recombination loss at interfaces, and thus enhancing the transport and extraction ability of charge carriers at the interfaces, targeting to top cell efficiency [32,33]. More recently, various successful interface modification strategies have been proposed and were concerned with solving the above obstacles, which produced a large number of emerging interfacial modifier materials including organic halide salt, i.e., phenylethylammonium iodide (PEAI), phenylmethylamine iodide (PMAI), butylammonium iodide (BAI) and 1-naphthylmethylamine iodide (NMAI) [34][35][36], organic molecules with specific functional groups [37][38][39][40][41], twodimensional materials [42][43][44] and others [45][46][47] capable to adjust the interface dynamics of charge carriers in PSCs and ultimately boost device performance and operational stability. Among these materials, the dipole molecules, such as poly(2-ethyl-2-oxazoline) (PEOz), polyethoxyvinylimine (PEIE) and polyethyleneimine (PEI), have aroused enough attention because of their versatility and ease to operate features.…”
Section: Introductionmentioning
confidence: 99%